Nicotinic acid adenine dinucleotide phosphate (NAADP) regulates autophagy in cultured astrocytes. - Pereira, G; Hirata, H; Fimia, G; do Carmo, LG; Bincoletto, C; Han, S; Stilhano, R; Ureshino, R; Bloor-Young, D; Churchill, G; Piacentini, M; Patel, S; et al. (2011)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a potent Ca(2+)-mobilizing messenger that in many cells releases Ca(2+) from the endolysosomal system. Recent studies have shown that NAADP-induced Ca(2+) mobilization is mediated by the two-pore channels (TPCs). Whether NAADP acts as a messenger in astrocytes is unclear, and downstream functional consequences have yet to be defined. Here, we show that intracellular delivery of NAADP evokes Ca(2+) signals from acidic organelles in rat astrocytes and that these signals are potentiated upon overexpression of TPCs. We also show that NAADP increases acidic vesicular organelle formation and levels of the autophagic markers, LC3II and beclin-1. NAADP-mediated increases in LC3II levels were reduced in cells expressing a dominant-negative TPC2 construct. Our data provide evidence that NAADP-evoked Ca(2+) signals mediated by TPCs regulate autophagy.